Respuesta :

The answer is C. 4x/3x^2+10x+3

[tex]\frac{ \frac{4}{x+3}}{ \frac{1}{x} +3} = \frac{ \frac{4}{x+3}}{ \frac{1}{x}+ \frac{3x}{x}} =\frac{ \frac{4}{x+3}}{ \frac{1+3x}{x} } = \frac{4}{x+3}* \frac{x}{1+3x}= \frac{4x}{(x+3)(1+3x)} = \frac{4x}{x+3 x^{2} +3+9x}[/tex] [tex]= \frac{4x}{3 x^{2} +10x+3} [/tex]

Answer:

The correct option is C.

Step-by-step explanation:

The given expression is

[tex]\frac{\frac{4}{x+3}}{(\frac{1}{x}+3)}[/tex]

[tex]\frac{\frac{4}{x+3}}{(\frac{1}{x}+3)}=\frac{\frac{4}{x+3}}{\frac{1+3x}{x}}[/tex]

The complex faction can be simplified as

[tex]\frac{(\frac{a}{b})}{(\frac{c}{d})}=\frac{a}{b}\times \frac{d}{c}[/tex]

[tex]\frac{\frac{4}{x+3}}{(\frac{1}{x}+3)}=\frac{4}{x+3}\times \frac{x}{1+3x}[/tex]

[tex]\frac{\frac{4}{x+3}}{(\frac{1}{x}+3)}=\frac{4x}{(x+3)(1+3x)}[/tex]

[tex]\frac{\frac{4}{x+3}}{(\frac{1}{x}+3)}=\frac{4x}{x(1+3x)+3(1+3x)}[/tex]

[tex]\frac{\frac{4}{x+3}}{(\frac{1}{x}+3)}=\frac{4x}{x+3x^2+3+9x}[/tex]

[tex]\frac{\frac{4}{x+3}}{(\frac{1}{x}+3)}=\frac{4x}{3x^2+10x+3}[/tex]

Therefore the correct option is C.